2011
DOI: 10.1055/s-0031-1280455
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntiallergic Effects of Aqueous Fermented Preparations fromCitrusandCydoniafruits

Abstract: This study aimed to investigate the immunomodulatory and antiallergic properties of preparations from lemon, Citrus medica L. (citrus), and quince, Cydonia oblonga Mill. (Cydonia), which are used in pharmaceutical products to treat patients suffering from allergic disorders. Preparations were analyzed with respect to their impact on the degranulation capacity from basophilic cells as well as mediator release from activated human mast cells in vitro, including IL-8 and TNF- α secretion. The results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
0
11
1
3
Order By: Relevance
“…HPLC analysis of the study medication. Unneeded samples of the study medication were freeze dried and analyzed by PhytoLab GmbH (Vestenbergsgreuth, Germany) on content of eriocitrin and hesperidin as main active substances of C. limon (Caristi et al, 2003;Qiao et al, 2014) and chlorogenic acid derivates (Huber et al, 2012) as characteristic active components of the Cydonia oblongata component.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC analysis of the study medication. Unneeded samples of the study medication were freeze dried and analyzed by PhytoLab GmbH (Vestenbergsgreuth, Germany) on content of eriocitrin and hesperidin as main active substances of C. limon (Caristi et al, 2003;Qiao et al, 2014) and chlorogenic acid derivates (Huber et al, 2012) as characteristic active components of the Cydonia oblongata component.…”
Section: Methodsmentioning
confidence: 99%
“…The effective in vitro concentrations (0.2-0.8 mg/mL) were in a range that could be reached by topical application as nasal spray. Furthermore, the lemon and quince components had in vitro differential and synergistic antiallergic effects (Baars et al, 2012;Huber et al, 2012). So far efficacy in humans has only been investigated in two (n = 12, n = 140) observational studies (Baars and De Bruin, 2005;Rother and Oexle, 2008) and a small (n = 23) randomized trial comparing the nasal and subcutaneous routes of application (Baars et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Test modalities were described earlier [19]. A total of 10 5 HMC-1 cells were incubated in a 96-well plate for 30 min with different extract concentrations.…”
Section: Il-8 Release From Hmc-1 Cellsmentioning
confidence: 99%
“…Aqueous preparations from whole quince fruits have been reported to be effective to treat allergic disorders [9]. Finally, a lipophilic quince extract was demonstrated to exhibit skin moisturizing properties [10]. Moreover, in the work by Umar et al [11] it is shown that Cydonia obonga (fruit and leaves) could regulate the blood lipid metabolism in using hyperlipidemic rat models while removing the oxygen free radicals and improving the antioxygenic potentials.…”
Section: Introductionmentioning
confidence: 99%